2016
DOI: 10.1016/j.ihj.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Do medical conferences have a role to play? Sharpen the saw

Abstract: Medical conferences are supposed to fulfill a critically important role in the ongoing education of physicians, technicians, nurses, and other health care providers. There are many functions which these conferences meet apart from merely imparting education: sharpening the skills, ability to interact with peers and KOLs, trying new equipment, evolving novel and locally relevant ideas, developing consensus in contentious areas all leading to improvement in health-care delivery, and patient outcomes. However, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 5 publications
1
42
0
1
Order By: Relevance
“…“The congresses enable health-care professionals to keep up-to-date with important research, learn directly from experiences and “trials and errors” of others, share best practices, and develop new skills and techniques. All of these have a direct impact on our daily clinical practice, helping us to improve safety and equality of care” [ 87 ]. “Exposure to other professionals may motivate the physicians to improve their performance and adapt continuous learning through the course of their careers” [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“The congresses enable health-care professionals to keep up-to-date with important research, learn directly from experiences and “trials and errors” of others, share best practices, and develop new skills and techniques. All of these have a direct impact on our daily clinical practice, helping us to improve safety and equality of care” [ 87 ]. “Exposure to other professionals may motivate the physicians to improve their performance and adapt continuous learning through the course of their careers” [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of these have a direct impact on our daily clinical practice, helping us to improve safety and equality of care” [ 87 ]. “Exposure to other professionals may motivate the physicians to improve their performance and adapt continuous learning through the course of their careers” [ 87 ]. Demonstration of regular attendance at conferences is therefore to be considered an obligatory requirement for surgeons in an accredited/certified hernia center [ 5 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…But today, because of these congresses with a large number of individuals and lack of respect for some of the important aspects, they are not adequate enough. 24 Another important issue mentioned by the participants and especially the teachers of the discipline was the generation gap between the students and the teachers. The results of a study by Alkatan on the effect of factors related to the preceptor and generation gap on education in the residency period showed that from among the three categories of factors related to preceptor qualifications and skills, the most important ones were behavioral patterns and generation gap.…”
Section: Discussionmentioning
confidence: 99%
“…Medical conferences play a major role for professionals in continuing their education. 1 They provide unique learning resources and career-building opportunities, such as selfpromotion and face-to-face interaction with the hosts and experts. 2 However, time consumption and high costs may limit participants.…”
mentioning
confidence: 99%